Early diagnosis of SARS Coronavirus infection by real time RT-PCR - Poon, Leo L.M. (J Clin Virol, 2003)
Background: A novel coronavirus was recently identified as the aetiological agent of Severe Acute Respiratory Syndrome (SARS). Molecular assays currently available for detection of SARS-coronavirus (SARS-Cov) have low sensitivity during the early stage of the illness. Objective: To develop and evaluate a sensitive diagnostic test for SARS by optimizing the viral RNA extraction methods and by applying real-time quantitative RT-PCR technology. Study design: 50 nasopharyngeal aspirate (NPA) samples collected from days 1–3 of disease onset from SARS patients in whom SARS CoV infections was subsequently serologically confirmed and 30 negative control samples were studied. Samples were tested by: (1) our first generation conventional RT-PCR assay with a routine RNA extraction method (Lancet 361 (2003) 1319), (2) our first generation conventional RT-PCR assay with a modified RNA extraction method, (3) a real-time quantitative RT-PCR assay with a modified RNA extraction method. Results: Of 50 NPA specimens collected during the first 3 days of illness, 11 (22%) were positive in our first generation RT-PCR assay. With a modification in the RNA extraction protocol, 22 (44%) samples were positive in the conventional RT-PCR assay. By combining the modified RNA extraction method and real-time quantitative PCR technology, 40 (80%) of these samples were positive in the real-time RT-PCR assay. No positive signal was observed in the negative controls. Conclusion: By optimizing RNA extraction methods and applying quantitative real time RT-PCR technologies, the sensitivity of tests for early diagnosis of SARS can be greatly enhanced.